Does immune priming in Galleria mellonella reveal plastic mechanisms for survival? - Terán-Murillo, Fátima; Ghosh, Enakshi; Rantala, Markus J.; Krams, Indrikis; Krams, Ronald; Contreras-Garduño, Jorge (Elsevier BV, 2025)
Immune priming enhances protection in invertebrates upon secondary exposure to specific pathogens. Despite significant advances in understanding this phenomenon, it remains unclear whether the elevated defense observed through priming arises from identical or distinct effector-mediated responses within the same species. To address this, we used the model species Galleria mellonella from two geographically distinct origins (Siberia and Mexico), both of which exhibited immune priming with enhanced survival. We measured five immune effectors in primed individuals to investigate whether the mechanisms behind immune priming were conserved. Remarkably, we identified distinct effector responses associated with immune priming between the two groups. Individuals of Siberian origin exhibited an increased total hemocyte count, and a higher number of live hemocytes in primed individuals. In contrast, individuals of Mexican origin demonstrated a higher lytic activity and a higher level of hydrogen peroxide production in the priming group compared with control. Phenoloxidase activity did not significantly differ across treatments in either group. Our findings suggest that G. mellonella from different origins achieve similar survival through different physiological effectors. These results highlight the diversity of immune priming mechanisms within a single species and support the idea that the immune priming mechanisms in invertebrates may be plastic within and across species.